Strategies for visualizing inflammation. Issue 1 (11th August 2020) - Zhang, Xinping; Liu, Xiaoyang; Guo, Yuxin; Wu, Fu‐Gen
Abstract: As a basic innate immune response to the disordered tissue homeostasis, inflammation is related to the pathogenesis of multiple diseases, including bacterial infections, atherosclerosis, neurodegenerative diseases, and cancers. It is also a pivotal feature of some metabolic disorders such as diabetes and obesity. The visualization of in vivo inflammations can help us to comprehend the pathogenesis of these diseases and develop new solutions to diagnose them. Over the past few decades, a variety of strategies (eg, computed tomography, magnetic resonance imaging [MRI], and ultrasound [US] imaging) have been utilized for visualizing inflammations by imaging the structural changes of inflammatory tissues. Moreover, many recent studies have focused on some probes that can target or localize the inflammatory sites by specific binding to inflammation‐related molecules, being internalized by inflammatory cells, or becoming detectable only under inflammatory conditions. These probes can also be applied to visualize inflammations by MRI, positron emission tomography, single‐photon emission computed tomography, photoacoustic imaging, optical imaging (eg, fluorescence imaging, bioluminescence imaging, and chemiluminescence imaging), contrast‐enhanced US imaging, and the combined use of the abovementioned methods. This review not only summarizes the existing strategies for visualizing inflammations, but also discusses the limitations of the present strategies and the future directions on the development of new strategies for realizing the in vivo inflammation visualization. Abstract : In this review, the authors have summarized that the recent progress in visualizing inflammations via various strategies and techniques, list the applications and limitations of them, and discuss the potential future directions for realizing better inflammation visualization.